DISEMINASI TEKNOLOGI PENGOLAHAN KOMPOS MENGGUNAKAN MIKROORGANISME LOKAL (MoL) DARI BAHAN ALAM SEBAGAI MEDIA DEKOMPOSER ALAMI - Said, M.I.; Utamy, R.F.; Syawal, S. (Buletin Udayana Mengabdi; Vol 23 No 4 (2024): Buletin Udayana MengabdiDO - 10.24843/BUM.2024.v23.i04.p11, 2023)
The increase in the use of chemical fertilizers on agricultural land has occurred more rapidly since the green revolution era. The use of chemical fertilizers is increasingly worrying because it has a huge impact on the survival of living things. The use of organic fertilizers such as compost is an alternative that can be selected to reduce the use of chemical fertilizers. Compost is produced from a mixture of organic materials, both organic matter derived from livestock and organic matter from plants. The compost process technology needs to be disseminated to the community, especially farmers. This activity aims to increase the technological knowledge capacity of members of farmer/livestock groups in utilizing cattle feces waste. Technology dissemination activities were carried out at the “Balumbungan” Farmer/Livestock Group in Bontonompo Village, Bontonompo District, Gowa Regency. The application of local microorganisms (LoM) from natural materials (rice waste) as a decomposer has been applied in the process of making compost made from cow feces combined with laying hen feces. Rice waste contains carbohydrates which are a good source of energy for the survival of microorganisms. Utilization of LoM as a decomposer in the fermentation process of organic materials is an attempt to utilize natural materials that have been wasted so far. Rice waste is a good growth medium for bacteria and fungi that are important for plants. The final result of the activity is increasing partner capacity in utilizing fecal waste into compost.   Keywords: compost, dissemination, feces, decomposer, organic fertilizer